التزام المؤسسات الصيدلانية بتتبع منتجاتها الصيدلانية - خضير,عبدالكريم; سلخ,محمد لمين (University of Eloued جامعة الوادي, 2024)
Abstract: Counterfeit or inferior pharmaceutical products pose a major challenge to governments, given the devastating effects they have on the health and safety of citizens, so it is the duty of states to provide a measure of security and safety related to the medicines and pharmaceutical products they take . Therefore, pharmaceutical traceability has been introduced as a pharmacovigilance mechanism and a solution that governments are working on, in cooperation with companies involved in the pharmaceutical industry and production, to ensure the safety of supply chains from the transit of counterfeit, inferior or unknown origin pharmaceutical products, including medicines, to reach the hands of the consumer . تشكل المنتجات الصيدلانية المزيفة أو الرديئة تحد كبير للحكومات، نظرا للأثار المدمرة التي تتركها على صحة المواطنين وسلامتهم ، اذا من واجبات الدول توفير قدر من الأمن والسلامة تتعلق بما يتناولونه من أدوية ومنتجات صيدلانية. من هنا استحدث التتبع الصيدلاني كآلية من آليات اليقظة الدوائية وحلا من الحلول التي تعمل على تجسيدها الحكومات بالتعاون مع الشركات المتدخلة في صناعة وإنتاج الأدوية، لضمان سلامة سلاسل التوريد من عبور تلك المنتجات الصيدلانية المزيفة أو الرديئة أو مجهولة المصدر، بما فيها الأدوية ووصولها الى يد المستهلك.
Keywords: آليات اليقظة الدوائية; سلامة سلاسل التوريد; مسار المنتج الصيدلاني; Enterprise Pharmaceuticals; Pharmaceutical Products; Pharmaceutical Traceability; Pharmacovigilance; Safety Supply chains. Pharmaceutical product pathway